2017
DOI: 10.3389/fnins.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Increased Testosterone Decreases Medial Cortical Volume and Neurogenesis in Territorial Side-Blotched Lizards (Uta stansburiana)

Abstract: Variation in an animal's spatial environment can induce variation in the hippocampus, an area of the brain involved in spatial cognitive processing. Specifically, increased spatial area use is correlated with increased hippocampal attributes, such as volume and neurogenesis. In the side-blotched lizard (Uta stansburiana), males demonstrate alternative reproductive tactics and are either territorial—defending large, clearly defined spatial boundaries—or non-territorial—traversing home ranges that are smaller th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 137 publications
(194 reference statements)
0
7
0
Order By: Relevance
“…The processes that characterize neurogenesis are subject to hormonal regulation, and therefore the influence of sex steroid hormones (or other sexually dimorphic endocrine factors, including glucocorticoid “stress” hormones) on cell proliferation and migration may contribute to the sex differences reported here (see reviews in Balthazart and Ball, 2016 ; Dunlap, 2016 ; Mahmoud et al, 2016 ; Powers, 2016 ). For example, treatment of territorial, but not non-territorial male side-blotched lizards ( Uta stansburiana ) with testosterone decreased the volume of the medial cortex and reduced the number of doublecortin-positive cells, an indicator of immature, migrating neurons (LaDage et al, 2017 ). Pellegrini et al ( 2007 ) showed that radial glial cells in the zebrafish forebrain express aromatase, the enzyme that synthesizes estrogens from androgens.…”
Section: Discussionmentioning
confidence: 99%
“…The processes that characterize neurogenesis are subject to hormonal regulation, and therefore the influence of sex steroid hormones (or other sexually dimorphic endocrine factors, including glucocorticoid “stress” hormones) on cell proliferation and migration may contribute to the sex differences reported here (see reviews in Balthazart and Ball, 2016 ; Dunlap, 2016 ; Mahmoud et al, 2016 ; Powers, 2016 ). For example, treatment of territorial, but not non-territorial male side-blotched lizards ( Uta stansburiana ) with testosterone decreased the volume of the medial cortex and reduced the number of doublecortin-positive cells, an indicator of immature, migrating neurons (LaDage et al, 2017 ). Pellegrini et al ( 2007 ) showed that radial glial cells in the zebrafish forebrain express aromatase, the enzyme that synthesizes estrogens from androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent‐centric views and associated bias are frequently questioned 3 . Adult neurogensis and RSA were characterised in fishes, reptiles, birds, and the majority of wild mammals 120‐125 . Thus adult neurogenesis seems to be evolutionarily conserved, driven by the needs of environmental adaptations.…”
Section: Identifications Of Rsa and Astrogliamentioning
confidence: 99%
“…3 Adult neurogensis and RSA were characterised in fishes, reptiles, birds, and the majority of wild mammals. [120][121][122][123][124][125] Thus adult neurogenesis seems to be evolutionarily conserved, driven by the needs of environmental adaptations. The details of adult neurogenesis in humans (especially in the hippocampus), however, remain to be elucidated.…”
Section: Animal Models and Human Neurogenesismentioning
confidence: 99%
“…Following previous methods in this species [LaDage et al, 2009[LaDage et al, , 2013[LaDage et al, , 2017, brains were sectioned on a cryostat (Leica CM 3050S, -20°C) in the coronal plane every 50 μm, and every other section was mounted and Nissl-stained with thionin to visualize the brain region boundaries (Fig. 2a) and the VPA neuron somas (Fig.…”
Section: Brain Processing and Analysismentioning
confidence: 99%
“…Specifically, the VPA (Fig. 2a) and remainder of the telencephalon (i.e., total telencephalon volume minus VPA volume) were outlined around their boundaries (contoured) within the software to assess if any population effects were specific to the VPA or representative of global changes within the brain [LaDage et al, 2009[LaDage et al, , 2013[LaDage et al, , 2017. We contoured both the left and right hemispheres to account for lateralization, as some previous studies have demonstrated differential activation between the left and right amygdala in mammals [reviewed in Baas et al, 2004].…”
Section: Brain Processing and Analysismentioning
confidence: 99%